Pengelolaan Peternakan Ayam Ras Petelur dalam Meningkatkan Pendapatan Ditinjau dari Manajemen Bisnis Syariah - Sulistyowati; Neny Romadhona Nurhadija Putri (Al-Muraqabah: Journal of Management and Sharia Business, 2022)
The purpose of the research in this article is to cultivate livestock to obtain optimal benefits and breeding results. The research method uses a qualitative descriptive approach with field research data collection, namely observation, interviews, and documentation. This study describes the management of laying hens in Ngrembang Hamlet, Kayunan Village, Plosoklaten District, which includes maintaining, caring for, regulating, maintaining the health of livestock, and taking benefits from livestock. The location of the farm is quite strategic and in accordance with the regulations for the establishment of laying hens. The facilities and infrastructure are fully available, the income obtained increases after the feed is measured according to the brochure from the breeder. In the management of laying hens farms there is no strict supervision, resulting in feed theft, theft of chickens that are ready to lay eggs, and employees when sorting eggs mixing eggs of good quality with eggs of poor quality. Farm owners do business not only to enrich themselves but for reasons of charity by giving more salary or eggs, then empowering the surrounding community by recruiting as employees, and always distributing eggs to all villagers every year.